The impact of the authors biography on the style, topics, and characters of his or her books: What made Ernest Hemingway write A Moveable Feast (Texas Journal of Philology, Culture and History, 2025)
This article explores the relationship between Ernest Hemingways biography and his literary production, focusing on the posthumously published memoir A Moveable Feast. The work is a reflective portrayal of Hemingways years in Paris during the 1920s and demonstrates how his personal life, experiences with contemporaries, and struggles with identity shaped the style, topics, and characters of his writing. By examining Hemingways biography and analyzing the text, the article highlights how memory, nostalgia, and artistic identity converge in his late work